Advanced Signaling Support for IP-based Networks - Röhricht, Martin (KIT Scientific Publishing, 2013)
This work develops a set of advanced signaling concepts for IP-based networks. It proposes a design for secure and authentic signaling and provides QoS signaling support for mobile users. Furthermore, this work develops methods which allow for scalable QoS signaling by realizing QoS-based group communication mechanisms and through aggregation of resource reservations.